Intergenerational transmission of self-employed status in the informal sector: a constrained choice or better income prospects? Evidence from seven West-African countries - Laure Pasquier-Doumer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Abstract Social reproduction is the highest for self-employed as shown by an extensive literature from developed and developing countries. Very few studies however document the reason for this high intergenerational correlation of the self-employed status. The rare studies that have been done concern the US and show that children of self-employed benefit from an advantage when they are themselves self-employed. The purpose of this paper is to test in the African context if the second-generation of self-employed has an advantage related to the first-generation. It aims at highlighting the debate between two visions: the first of informal sector as the less-advantaged sector of a dualistic labour market, and the second as a sector of personal choice and dynamic entrepreneurship. Using 1-2-3 surveys collected in the commercial capitals of seven West African countries in 2001-2002, this paper shows that the second-generation of informal self-employed does not have better outcomes than the first one, except when they choose a familial tradition in the same sector of activity. Thus, in the African context, having a self-employed father does not provide any advantage in terms of profit or sales and is not sufficient for the transmission of a valuable informal human capital. On the other hand, informal entrepreneurs who have chosen a specific enterprise based on familial tradition have a comparative advantage. Their comparative advantage is partly explained by the transmission of enterprise-specific human capital, acquired thanks to experiences in the same type of activity and by the transmission of social capital that guarantees a better clientele and a reputation.
Keywords: L26; J24; J62; 330; informal sector; entrepreneurship; intergenerational link